Pengembangan Suplemen Bahan Ajar Ebook Berbasis Kearifan Lokal di KALBAR Bermuatan Nilai Karakter - Muhammad Robi Harjuni; Siti Halidjah; Dyoty Aulia Vilda Ghasya (Journal on Education, 2023)
This study aims to develop a supplement to Ebook Teaching Materials Based on Local Wisdom in West Kalimantan with Character Values. This study uses research and development (R&D) methods with a mixed methods approach. While the model used is the Borg & Gall model with 7 steps that have been modified. Quantitative data was obtained from the results of product assessments by the validator and the results of filling out the practicality questionnaire by teachers and students. Qualitative data were obtained from suggestions and notes by validators, teachers and students. Research instruments in the form of interview guidelines and questionnaires. The level of product feasibility is based on the results of an assessment by the design, material and language expert validator. While the practicality level of the product is based on the results of the assessment by teachers and students. The results of validation by design experts with the criteria of "valid" which means that they have achieved the qualification of "proper" for use. The results of validation by material experts with the criteria of "very valid" which means that they have achieved the qualification of "very feasible" for use. The results of validation by linguists with the criteria of "very valid" which means that they have achieved the qualification of "very feasible" for use. The results of the feasibility and practicality of Ebook Teaching Materials Based on Local Wisdom in West Kalimantan on a small scale and large scale with very practical and very feasible criteria.